Stretch-induced structural transition of linear low-density polyethylene during uniaxial stretching under different strain rates. (4th June 2021) - Feng, Shengyao; Lin, Yuanfei; Yu, Wancheng; Iqbal, Obaid; Habumugisha, Jean Claude; Chen, Wei; Meng, Lingpu; Lu, Ai; Li, Liangbin
Abstract: The structural evolutions of linear low-density polyethylene (LLDPE) are investigated by in-situ synchrotron radiation wide-angle X-ray diffraction (WAXD) during tensile deformation over a wide strain rates range from 0.005 to 250 s −1 . The phase transition mechanism is discussed by combining the phase diagram in 2D true stress ( σ true )-strain rate ( ε ˙ ) space with the evolutions of several micro-structural parameters, such as the crystallinity ( χ c ), crystal sizes ( L 110, L 200 ) and lattice parameters ( a O, b O ). The true stress space can be roughly divided into three regions by two critical true stresses at the onset formation of the monoclinic ( σ M-onset ) and the hexagonal ( σ H-onset ) crystals. In region I where only orthorhombic crystals exist, lattice distortion under the effects of stress plays a dominant role. In region II, the martensitic transformation from orthorhombic to monoclinic crystals occurs and monoclinic crystals load the main tensile stress. In region III, stress-induced melt recrystallization occurs and hexagonal crystals appear. In addition, the effects of strain rate on the stress-induced melt crystallization and lattice deformation are also discussed. This study on LLDPE films might aid to deepen the understanding of structural evolutions during real post-stretching process. Graphical abstract: Image 1 Highlights: The structural evolution of LLDPE films during uniaxial stretching over a wide strain rates range have been investigated with in-situ WAXD. The occurrence of Martensitic transformation from orthorhombic to monoclinic crystals seems to coincide with the yield point. The onset formation of hexagonal crystals is related with the onset point of strain hardening. The formation of monoclinic and hexagonal phases is accompanied by the redistribution of microscopic stress inside the film. The stress-induced melt-crystallization and lattice deformation seems more obvious and uniform at low strain rates than at high strain rates.